Torneuma penaensis sp. n. from the Algarve, Portugal (Coleoptera, Curculionidae) - Germann, Christoph; Braunert, Carlo (Zootaxa, 2014)
A new species of the genus Torneuma Wollaston, 1860 is described from the Algarve region in Portugal. It is the third species of the genus known from Portugal besides T. longipenne Pic, 1910 and T. serpentinum Stüben, 2007.